Perbedaan Harga Diri Mahasiswi Muslim yang Berhijab dan Tidak Berhijab - Hendra Choirul Anam; Nicholas Simarmata (Jurnal Psikologi Integratif, 2017)
Self-Esteemisthe one's personalfeeling that he/she is valuable oruseful andself-confident that is based onmore than justthe reputation and prestige (Maslow, 1970). Individual, whichin this caseisMuslimfemale student who wear hijab, has higher self-esteemthanMuslim female studentwho does not wear hijab. This is becauseMuslimfemale studentwho wear hijab has been ready to fulfill the obligationin Islam religion, thatis requires to wear hijabin dressingfor women. Muslim female student who does notwear hijab has lower self-esteem because shefeels not ready tofulfill her religious obligation. There fore, researcher sare interested in examining whether thereisa difference between theself-esteemof Muslim female student who wear the hijab and not. This research is a comparative quantitative research whose subjects are Muslim students in Surabaya and Denpasar.  Data were collected using the Self-Pricing scale. The sampling technique is purposive sampling. Validity used is the validity of the content (logical and look).  The validity of the aitem moves from 0.3202 to 0.743. Reliability scale Self-esteem is 0.916. Data were analyzed by using Independent sample t-test statistic test.  The result is that there is no difference in self-esteem between Muslim students, both hijab and unlawful as evidenced by their probability value (p) of 0.233 (greater than 0.05).